2010
DOI: 10.1097/tp.0b013e3181c478fd
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Heparin Infusions Peritransplant Substantially Improve Single-Donor Clinical Islet Transplant Success

Abstract: Peritransplant intensive insulin and heparin enhances islet transplantation outcomes likely related in part to mitigation of the effects of the instant blood-mediated inflammatory reaction, combined with islet rest and avoidance of inflammation. It would be important to further investigate the effects of peritransplant insulin and heparin infusions on islet engraftment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 28 publications
(30 reference statements)
2
91
1
Order By: Relevance
“…Strong deposition of xenoreactive antibody combined with C1q, C3 and C4 was observed. LMWDS was more effective than heparin in minimizing IBMIR (29). In allogenic and xenogenic islet studies, we observed mild elevation of sC5b-9 levels during islet infusion and at days 3-7; however, little C3a and C4d response during the peritransplant period was seen.…”
Section: Moberg Et Almentioning
confidence: 81%
“…Strong deposition of xenoreactive antibody combined with C1q, C3 and C4 was observed. LMWDS was more effective than heparin in minimizing IBMIR (29). In allogenic and xenogenic islet studies, we observed mild elevation of sC5b-9 levels during islet infusion and at days 3-7; however, little C3a and C4d response during the peritransplant period was seen.…”
Section: Moberg Et Almentioning
confidence: 81%
“…Although the Edmonton protocol introduced various suggestions for the improvement of islet transplantation, 1 there is a concern of deteriorating graft function over time. 2 In addition, while single-donor islet transplantation success has been achieved, [3][4][5] most centers still rely on multiple donor organs to achieve initial insulin independence. 6 A possible explanation for this problem is that many islets are destroyed immediately following transplantation, before a vascular network is reestablished.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve patients received 1 implant, 38 patients 2 implants within 3 months (IQR 2.4-3.5 months) after the first implantation and 1 patient received 3 implants (at 2.5 and 5 months posttransplantation). Based on a possible beneficial effect of intravenous heparin infusion peritransplant as reported by Koh et al (13), heparin was administered in 3 patients undergoing laparoscopic implantation at 70 U/kg using continuous infusion of heparin containing saline (10U/ml) at 500 U/h (50ml/h) up to 24 hours post-transplantation (PT).…”
Section: Preparation Of Islet Beta Cell Grafts and Transplantationmentioning
confidence: 99%